DOMESTICATION AND FOREIGNIZATION IN THE TRANSLATION OF CHILDREN’S LITERATURE - M. Xamidova (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article studies domestication and foreignization in the translation of children’s literature. The topic is important because children’s books carry language, culture, values, humor, and daily life together. When a story is translated, the translator must decide whether to make the text closer to the young reader or preserve the foreign color of the source text. The article analyzes how this problem appears in culture- specific items, food names, proper names, and short rhythmic lines. The research is based on descriptive translation analysis, close reading, and comparative textual analysis. Classical works by Lawrence Venuti, Riitta Oittinen, Gillian Lathey, Göte Klingberg, and Emer O’Sullivan are used together with newer studies by Haidee Kruger, Fenik M. Ghafur, and Kaveh Bassiri. Short extracts from well-known children’s stories are examined to show how each strategy changes meaning, tone, rhythm, and cultural atmosphere. The main result is that children’s literature translation usually works best when a balanced method is used: very difficult items may be adapted, but important cultural signs should remain visible.